A techno-economic assessment framework for hydrogen energy storage toward multiple energy delivery pathways and grid services. (15th June 2022) - Wu, Di; Wang, Dexin; Ramachandran, Thiagarajan; Holladay, Jamie
Abstract: Hydrogen energy storage (HES) transforms and stores electric energy from the grid into hydrogen, and supplements other energy storage and demand response resources in addressing challenges in renewable-intensive power systems. Understanding how to optimally utilize an HES system to maximize its economic benefits from stacked value streams is highly important to its development and deployment. This paper presents a techno-economic assessment framework for an HES system considering three common energy delivery pathways and multiple grid and end-user services. Models are developed to capture the operational capability, flexibility, and constraints associated with hydrogen production, compression, storage, and utilization as well as different grid services in an economic assessment. To define the technically achievable benefits, an optimal dispatch formulation is proposed to maximize the economic benefits over a representative year with an hourly time step considering the trade-offs among different value streams. Representative case studies are designed and carried out to show how system configuration, energy delivery pathways, and grid services may affect economic benefits. It was found that value streams from bundling grid services account for up to 76% of the total benefits and are critical for an HES project to be financially viable. Highlights: An assessment framework is proposed for hydrogen energy storage considering stacked value streams. Multiple energy delivery pathways and grid services are modeled. Key techno-economic characteristics of hydrogen energy storage are captured. A mixed-integer linear programming formulation is proposed to define technically achievable benefits. Comprehensive analyses are performed to identify key factors that affect cost-effectiveness.